Switched Reluctance Motor Concept, Control and Applications - Tahour, Ahmed; Ghani Aissaoui, Abdel (IntechOpen, 2017)
In the last years, the switched reluctance machines (SRMs) have been the subject of significant developments. SRMs are gaining much interest because of their simplicity in structures, high-output power, high starting torque, wide speed range, rugged and robust construction, reliability, and low manufacturing costs, which make these machines viable for many applications. SRMs include machines of different structures whose common property is the significant variation in the shape of the air gap during rotation. The use of advanced control technologies makes possible the integration of the mechanical and electrical conversion systems in their optimal mode of operation. Different strategies of control can be applied to SRMs, depending on their mode of functioning and the purpose of their applications. The goal of this book is to present recent works on concept, control, and applications in switched reluctance machines.